Metode Penelitiaan Berspektif Jender Tentang Literatur Islam - Nasaruddin Umar (Al-Jami'ah Research Centre, 1999)
This article explains about how to conduct research on Islamic literature in the perspective of gender. Gender bias in reading understanding Qur'an and Hadis is due to several reasons. Firstly, the codification of Qur'an in a single way of reading prevents the other version of understanding which has no gender bias. Secondly, the meaning of certain words (mufradād) are often debatable. Thirdly, the reference of pronoun (Domir) is often not certain. Fourthly, the limit of exception (Mustasna) is often debatable. Moreover, the reference world ('Atf) wau has several meanings. Sixthly, the structure of Arabic language is based on Arabic patriarchal culture. Furthermore, the bias also come from Arabic dictionaries which only provide meaning that have gender bias. Eighthly, some methods of exegetes produce the understanding of the text which has gender bias. In addition, the influence of Israeli stories (isrā’ilyyāt) in understanding Qur'anic verses cause also gender bias. Finally, the contributes of Fiqh Books which are influenced by local cultures contributes to this gender bias.